2018
DOI: 10.1029/2017jf004578
|View full text |Cite
|
Sign up to set email alerts
|

Development and Application of a Large‐Scale, Physically Based, Distributed Suspended Sediment Transport Model on the Fraser River Basin, British Columbia, Canada

Abstract: Modeling sediment transport through large basins presents a challenging problem. The relation between water flux and sediment load is complex, and substantial erosion and transport can occur over small spatial and temporal scales. Analysis of large‐scale basins often relies on lumped empirical models that do not consider spatial or subannual variability. In this study, we adapt a small‐scale, mechanistic, distributed suspended sediment transport model for application to large basins. The model is integrated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 83 publications
(163 reference statements)
1
22
0
Order By: Relevance
“…Run‐off within the mountainous regions of the basin is snowmelt driven, whereas the interior plateau hosts both hybrid and rain‐dominated regimes (Figure ). Tsuruta et al () found that hillslope erosion and in‐channel transport within the FRB were driven primarily by run‐off. The study also concluded that although the FRB's sediment supply was generated mainly within the Rocky and coastal mountains, sinks within these regions such as the Lillooet and Kamloops Rivers (Figure ) play an important role in the sediment load of the main stem of the Fraser.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Run‐off within the mountainous regions of the basin is snowmelt driven, whereas the interior plateau hosts both hybrid and rain‐dominated regimes (Figure ). Tsuruta et al () found that hillslope erosion and in‐channel transport within the FRB were driven primarily by run‐off. The study also concluded that although the FRB's sediment supply was generated mainly within the Rocky and coastal mountains, sinks within these regions such as the Lillooet and Kamloops Rivers (Figure ) play an important role in the sediment load of the main stem of the Fraser.…”
Section: Methodsmentioning
confidence: 99%
“…BCSD: bias corrected spatial disaggregation; BCGS: British Columbia Geological Survey; GCM: general circulation models; GMTED: global multi‐resolution terrain elevation data; ISRIC: International Soil and Reference Centre; THMB: terrestrial hydrology model with biochemistry; VIC: variable infiltration capacity. This figure is modified from figure 1 in Tsuruta et al ()…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations